2017
DOI: 10.4317/medoral.21809
|View full text |Cite
|
Sign up to set email alerts
|

Maxillofacial fracture epidemiology and treatment plans in the Northeast of Iran: A retrospective study

Abstract: BackgroundThe epidemiology of facial injuries varies based on lifestyle, cultural background and socioeconomic status in different countries and geographic zones. This study evaluated the epidemiology of maxillofacial fractures and treatment plans in hospitalized patients in Northeast of Iran (2015-2016).Material and MethodsIn this retrospective study, the medical records of 502 hospitalized patients were evaluated in the Department of Maxillofacial Surgery in Kamyab Hospital in Mashhad, Iran. The type and cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
23
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(64 citation statements)
references
References 58 publications
(91 reference statements)
5
23
2
4
Order By: Relevance
“…This result corroborates other studies which have suggested a 3:1 ratio; with 1 girl being affected for every three boys . Other studies have shown an even higher proportion with ratios up to 4:1 …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This result corroborates other studies which have suggested a 3:1 ratio; with 1 girl being affected for every three boys . Other studies have shown an even higher proportion with ratios up to 4:1 …”
Section: Discussionsupporting
confidence: 92%
“…Traffic accidents were ranked as the leading cause of oral‐maxillofacial trauma in children and adolescents worldwide with a prevalence of 20%. Additionally, an increase in road traffic accidents (around 40%) has been described in some countries which may be partially explained by poor adherence to laws and poor use of protective head gear, therefore increasing susceptibility to craniofacial injuries …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the incidence of nasal bone fractures vary by age, gender, geographic region, socioeconomic status, and culture . Nasal bone fracture etiology similarly varies by population, and includes most commonly sports trauma, assault, motor vehicle accidents, and falls …”
Section: Introductionmentioning
confidence: 99%